2010
DOI: 10.1093/jaoac/93.4.1192
|View full text |Cite
|
Sign up to set email alerts
|

Validated HPLC Determination of the Two Fixed Dose Combinations (Chlordiazepoxide Hydrochloride and Mebeverine Hydrochloride; Carvedilol and Hydrochlorothiazide) in Their Tablets

Abstract: Simple, rapid, and selective RP-HPLC methods with UV detection were developed for simultaneous determination of chlordiazepoxide hydrochloride and mebeverine hydrochloride (Mixture I) and carvedilol and hydrochlorothiazide (Mixture II). The chromatographic separation in both mixtures was achieved by using an RP-C8 (octylsilyl) analytical column. For Mixture I, a mobile phase composed of acetonitrile0.05 M disodium hydrogen phosphatetriethylamine (50 + 50 + 0.2, v/v/v), pH 2.5, was used; the detector wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…1) potent direct antispasmodic agent used mainly for the smooth muscles of the gastrointestinal tract and particularly effective against the colonic spasm [1] It is used in the treatment of abdominal pain and spasm associated with gastrointestinal disorders such as mucous colitis [2] Due to the vital importance of MV.HCl, there are many reported methods for its determination in its pharmaceutical formulations and in biological fluids. Among these methods are HPLC [3][4][5][6][7], spectrophotometry [8][9][10][11], GC-MS [12], and electrochemistry [13][14][15][16]. On one side, most of the reported chromatographic is expensive method of analysis required a high maintenance cost, high acquisition cost, time-consuming procedures, senetive equilibration, it also may requires derivatization treatment prior to analysis and expensive grades of reagents, eluents, and equipment [3][4][5][6][7]12], On other side, there are some reported electrochemical methods based on potentiometry [13], square-wave anodic stripping voltammetry (SW-ASV) [14,16] and differential pulse voltammetry (DPV) [15] listed in (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) potent direct antispasmodic agent used mainly for the smooth muscles of the gastrointestinal tract and particularly effective against the colonic spasm [1] It is used in the treatment of abdominal pain and spasm associated with gastrointestinal disorders such as mucous colitis [2] Due to the vital importance of MV.HCl, there are many reported methods for its determination in its pharmaceutical formulations and in biological fluids. Among these methods are HPLC [3][4][5][6][7], spectrophotometry [8][9][10][11], GC-MS [12], and electrochemistry [13][14][15][16]. On one side, most of the reported chromatographic is expensive method of analysis required a high maintenance cost, high acquisition cost, time-consuming procedures, senetive equilibration, it also may requires derivatization treatment prior to analysis and expensive grades of reagents, eluents, and equipment [3][4][5][6][7]12], On other side, there are some reported electrochemical methods based on potentiometry [13], square-wave anodic stripping voltammetry (SW-ASV) [14,16] and differential pulse voltammetry (DPV) [15] listed in (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods are HPLC [3][4][5][6][7], spectrophotometry [8][9][10][11], GC-MS [12], and electrochemistry [13][14][15][16]. On one side, most of the reported chromatographic is expensive method of analysis required a high maintenance cost, high acquisition cost, time-consuming procedures, senetive equilibration, it also may requires derivatization treatment prior to analysis and expensive grades of reagents, eluents, and equipment [3][4][5][6][7]12], On other side, there are some reported electrochemical methods based on potentiometry [13], square-wave anodic stripping voltammetry (SW-ASV) [14,16] and differential pulse voltammetry (DPV) [15] listed in (Table 1). It is noticed that Potentiometry and SW-AdASV onto bare Carbon paste electrode CPE did not offer a sufficient sensitive quantitation limit of MV.HCl that can cover pharmacokinetic studies and therapeutic drug monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods including determination of CRV by its quenching effect on the luminescence of terbium complex in dosage form [19], spectrofluorimetric determination via derivatization with 7-Chloro-4-niritrobenzofurazon [20], and nonaqueous titration [21] have been described. Chromatographic methods have been reported such as validated HPLC determination of the fixed dose combination (CRV and hydrochlorothiazide) in their tablets [22], HPLC with fluorescence detection [23], and RP-HPLC method for monitoring of the photochemical stability of CRV and its degradation products [24]. A Chiral HPLCseparation and determination of CRV from human urine was also noticed [25].…”
Section: Introductionmentioning
confidence: 99%
“…From the literature survey it was concluded that only few RP-HPLC methods [1], have been reported for the determination of Mebeverine and Chlordiazepoxide in combination. Certain methods for the estimation of Mebeverine and Chlordiazepoxide in combined dosage forms include UV spectrophotometric method [2].…”
Section: Introductionmentioning
confidence: 99%